Changes in consumption during the covid-19 pandemic in Canada - Abiodun Anoba, Abibat Olaoluwa (Université d'Ottawa | University of Ottawa, 2021)
Consumption is a large component of Canada’s Gross Domestic Product (GDP) and as such, it is important to examine its changes as it relates to the ongoing pandemic. This paper studies how consumption changed during the pandemic in Canada. To reduce the number of COVID-19 cases, a mandatory lockdown was implemented. I analyze the household final consumption expenditure data of 2019 and 2020 using a linear regression model with dummy variables. The analysis is done in Canada, all the provinces, and the categories of consumption: goods and services. The result shows that there was a 7.22% decline in daily consumption in Canada after the lockdown. At the provincial level, Alberta, Newfoundland, and British Columbia had the most decline in daily consumption after the lockdown, 9.83%, 8.03%, and 7.71%, respectively. Quebec, Saskatchewan, and New Brunswick had the least decline in daily consumption after the lockdown, 5.4%, 5.94% and 5.98%, respectively. Daily consumption of services fell by 13.5% after the lockdown while the daily consumption of goods rose by 0.475% but it was statistically insignificant.